PELINDIAN UNSUR KALIUM (K) DAN NATRIUM (Na) MATERIAL VULKANIK HASIL ERUPSI GUNUNG MERAPI 2010 (Simulasi Laboratorium) - Taufiq Perak Sanjaya; Jauhari Syamsiyah; Dwi Priyo Ariyanto; Komariah Komariah (Caraka Tani: Journal of Sustainable Agriculture, 2014)
This research was conducted at the Greenhouse Laboratory of the Faculty of Agriculture, Sebelas Maret University Surakarta, in March 2011. The aim of the study was to determine the relationship between the rainfall (synthetic) the number of elements Potassium (K) and Sodium (Na) were leached in volcanic material from the eruption of Mount Merapi. This study used artificial rainfall simulation approach to treatment is based on the phenomenon of the eruption of Mount Merapi, Yogyakarta, Central Java by examining the leaching elements Sodium (Na) and Potassium (K) are swapped in the above-ground volcanic material Andisol. The experiments in this study using a completely randomized design (CRD) consisting of 3 to 5 treatments the sample depth artificial rain (water sprinkling) in 3 replications, namely 1 (22 mm x 1 day (22 mm)), 2 (22 mm x 10 days (220 mm)), 3 (22 mm x 20 days (440 mm)), 4 (22 mm x 30 days (660 mm)), 5 (22 mm x 45 days (990 mm)), and control ( 45 days field) with 3 replicates each. The variables measured were pH H2O, available K and Na, K and Na total, CEC, texture. Analysis of the data using the F test at the level of 95% or Kruskal-Wallis, to compare the mean between treatments using DMR test at the level of 95% or Mood Median, whereas to determine the relationship between variables used correlation test. The results showed that administration of rainfall of 22 mm / day is able to affect the leaching of potassium and sodium in the volcanic material from day 10. Leaching was significantly visible on day 30 with a decrease in available K and Na volcanic material at a depth of 0-15 cm in diameter (K 23.08%) (23.08% Na) and at a depth of 15-30 cm (K 21, 42%) (23.08% Na), and the addition of K and Na are available at a depth of >30 cm in the form of land Andisol (K 16.67%) (23.53% Na) from the previous treatment.